2014
DOI: 10.1002/bjs.9436
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancies between medical oncologists and surgeons in assessment of resectability and indication for chemotherapy in patients with colorectal liver metastases

Abstract: Resectability and indication for preoperative chemotherapy were assessed differently by medical oncologists and surgeons. The educational intervention resulted in more patients deemed resectable by both oncologists and surgeons, and less frequent indication for chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
9

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 32 publications
1
27
0
9
Order By: Relevance
“…Especially the expertise of colorectal, hepatobiliary, thoracic, and peritoneal surface surgeons next to medical and radiation oncologists, interventional radiologists, gastroenterologists, and pathologists should be available within the MDT . It has been shown that training sessions have a positive impact on the performance of MDTs with more metastatic patients deemed resectable . Our results confirm the quality of pathways pursued within the MDT due to the high rate of complete resections and the survival rate of more than 50%.…”
Section: Discussionsupporting
confidence: 75%
“…Especially the expertise of colorectal, hepatobiliary, thoracic, and peritoneal surface surgeons next to medical and radiation oncologists, interventional radiologists, gastroenterologists, and pathologists should be available within the MDT . It has been shown that training sessions have a positive impact on the performance of MDTs with more metastatic patients deemed resectable . Our results confirm the quality of pathways pursued within the MDT due to the high rate of complete resections and the survival rate of more than 50%.…”
Section: Discussionsupporting
confidence: 75%
“…In a virtual board meeting with 30 cases presented to 11 surgeons and 10 medical oncologists, surgeons considered CRLMs resectable more often than did medical oncologists. 6 Medical oncologists were more likely than surgeons to indicate preoperative chemotherapy, mostly in cases deemed unresectable. Interestingly, the proportion of cases considered unresectable and the indication for preoperative chemotherapy by both surgeons and medical oncologists decreased after an educational intervention outlining the latest resectability criteria.…”
Section: Discussionmentioning
confidence: 99%
“…5 Perhaps even more important, wide variability in definitions of resectable disease and referral patterns for patients with CRLMs have also been reported. [6][7][8] This study serves as a pilot to investigate an initial resectability assessment and specialty referral of patients with CRLMs across multiple oncologic specialties and subspecialties (general surgeons, colorectal surgeons, surgical oncologists and medical oncologists) compared to a panel of hepatobiliary surgeons.…”
Section: Résultatsmentioning
confidence: 99%
“…When patients are diagnosed in these hospitals they are discussed in multidisciplinary teams, where a specialist liver surgeons is not always involved in these meetings. Also the presence of a dedicated medical oncologist is demonstrated to be important in considering patients suitable for neo-adjuvant chemotherapy in patients with CRLM [37]. Jones et al [38] demonstrated that even in high-volume centers (UK cancer network), almost two-thirds of patients with tumors who were deemed unresectable by non-liver surgeons were considered potentially resectable by a panel of specialist liver surgeons.…”
Section: Discussionmentioning
confidence: 99%